Multisector Strategy in Addressing Noncommunicable Diseases in the Philippines - Valerie Gilbert T. Ulep; Melanie P. Aldeon; Nina Ashley O. dela Cruz (Philippine Institute for Development Studies (PIDS), 2013)
This report is a continuation of the discussion paper of the Philippine Institute for Development Studies entitled "Inequalities in Noncommunicable Diseases in the Philippines". The first technical paper is an analysis of the current status and social determinants of noncommunicable diseases (NCD). This report, on the other hand, focuses on potential NCD prevention and control strategies of the Department of Health (DOH) with wider multisector involvement.This report is divided into five chapters. Chapters I and II discuss the current status of noncommunicable diseases and existing policies and programs of the DOH. Chapter III introduces the potential roadmap of the NCD prevention and control program of the DOH. Chapter IV defines the roles and responsibilities of different bureaus within the health sector. Chapter V outlines the potential framework of the multisector strategy of the DOH.
Keywords: 330; Philippines; noncommunicable diseases; multisector collaboration; health system approach; supply and demand-side interventions